PREVALENCE AND RISK FACTORS OF SARCOPENIA IN PATIENTS WITH HUMAN IMMUNODEFICIENCY VIRUS - Putu Ayu Kevin Komala Dewi Mahayuna Putri; I Wayan Yuna Ariawan; I Wayan Eka Saputra (International Medical Journal Corp. Ltd, 2026)
Background : HIV patients have a life expectancy that is close to the life expectancy of the general population after using ARVs, so that increasing HIV patients suffer from age-related diseases and chronic inflammation, one of which is sarcopenia. Research on sarcopenia in HIV patients in Indonesia is still limited, so the author is interested in conducting this study with the aim of determining the prevalence and risk factors for sarcopenia in HIV patients. Method : A cross-sectional study conducted at Sanjiwani Hospital Gianyar on October 2025. This study included 125 HIV patients, aged 20-75 and receiving ARV for more than a year. Sarcopenia was determined based on the 2019 Asian Working Group for Sarcopenia (AWGS) criteria, health status based on questionnaires, measurments, and medical records. Logistic regression analysis was used to determine the risk of sarcopenia occurrence. Result : A total of 125 sampel consisted of 40.8% women, and 59.2% men with an average age of 48.35 ± 10.8 years. Most of them had suffered from HIV for more than 5 years (60%). The prevalence of sarcopenia was 20.8%. Risk factors for sarcopenia included advanced age (≥50 years, OR =6,01, female gender (OR=5,07). Conclusion : This prevalence of sarcopenia in HIV patients was 20.8%, advance age, female gender are risk factors for sarcopenia in HIV patients.